Occurrence, diversity and morphology of poroid wood decay by Ganoderma spp. from tropical moist deciduous forest region of Bangladesh - Mafia, M. I.; Aminuzzaman, F. M.; Chowdhury, Mohammad Salahuddin Mahmood; Tanni, Jannatul Ferdous (Journal of Agriculture and Natural Resources, 2020)
There are many hot spots in tropical moist deciduous forest region where wood decay fungi grow naturally. An investigation was carried out to collect, identify and preserve wood decay Ganoderma spp. on the basis of morphological characteristics from Pabna, Dhaka and Rajshahi under tropical moist deciduous forest region in Bangladesh during June to September 2016 and July to October 2017. This study was conducted to record the morphological variability, distribution, habitat and diversity of the Ganoderma population. A total of 40 Ganoderma samples were collected and identified to nine species under Ganodermataceae family. The samples were collected from the sites by walking through the area following standard method. The field data and laboratory analytical data was recorded during sample collection and in the laboratory, respectively.The highest density of occurrence (23%) was recorded for Ganoderma lucidum and Ganoderma oregonense followed by Ganoderma applanatum (20%), Ganoderma praelongum (19%), Ganoderma lesklokorka (18.5%), Ganoderma pfeifferi (17%), Ganoderma boninense (15%), Ganoderma lipsiense (13%) and Ganoderma tsugae (11%). The highest frequency of occurrence (10%) was recorded for Ganoderma applanatum and Ganoderma oregonense followed by Ganoderma lucidum (9%), Ganoderma pfeifferi (8%), Ganoderma boninense (8%), Ganoderma praelongum (7%), Ganoderma lesklokorka (7%),Ganoderma tsugae (6%) and Ganoderma lipsiense (5%). During survey, Koroi (Albizia procera), Aurjun (Terminalia arjuna), Sisso plant (Dalbergia sissoo), Neem (Azadirachta indica), Golden shower (Acacia auriculiformis) and Rain tree (Albizia lebbeck) were found as hosts of Ganoderma spp. The specimens were preserved in the SAU Herbarium of Macro Fungi (SHMF) and might be useful in mushroom breeding and development program for medicine and food industry sector in future.